2015
DOI: 10.3389/fmicb.2015.00050
|View full text |Cite
|
Sign up to set email alerts
|

Host response during Yersinia pestis infection of human bronchial epithelial cells involves negative regulation of autophagy and suggests a modulation of survival-related and cellular growth pathways

Abstract: Yersinia pestis (Yp) causes the re-emerging disease plague, and is classified by the CDC and NIAID as a highest priority (Category A) pathogen. Currently, there is no approved human vaccine available and advances in early diagnostics and effective therapeutics are urgently needed. A deep understanding of the mechanisms of host response to Yp infection can significantly advance these three areas. We employed the Reverse Phase Protein Microarray (RPMA) technology to reveal the dynamic states of either protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…The present study added a time-resolved perspective to many of those molecular events, such as ubiquitin and microtubule functions that were reported previously in the context of Y . pestis pathogenesis [13, 14, 35, 39, 40]. In fact, our previous publication [4] upheld ubiquitin and microtubule functions as two major networks potentially manipulated by Y .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study added a time-resolved perspective to many of those molecular events, such as ubiquitin and microtubule functions that were reported previously in the context of Y . pestis pathogenesis [13, 14, 35, 39, 40]. In fact, our previous publication [4] upheld ubiquitin and microtubule functions as two major networks potentially manipulated by Y .…”
Section: Resultsmentioning
confidence: 99%
“…Y . pestis was found to block autophagosomes in vitro by altering the functions of AKT, AMPK and p53 signaling [39]. An in vivo study observed a slightly different mechanism, where Y .…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways are associated with tumorigenesis and activated in a number of cancers (19). Yersinia pestis infection of HBECs has been associated with the negative regulation of autophagy via the observed decrease exhibited of p53 cytoplasmic localization and PI3K/AKT activation (31). Furthermore, plumbagin has been demonstrated to induce autophagy via the inhibition of the PI3K/AKT pathway in human non-small cell lung cancer cells (32) In the present study, the activation of p53 was significantly increased; however, AKT protein activation via phosphorylation was significantly decreased in pWHL-1-transfected HBECs when compared with the control and NC groups, indicating that HBoV induced HBEC autophagy predominantly through enhancing p53 activation and blocking AKT activation.…”
Section: Discussionmentioning
confidence: 99%
“…Another bacterium, Yersinia pseudotuberculosis , replicates intracellularly inside specific compartments called Yersinia -containing vacuoles (YCVs), which contain autophagy markers; however, YCVs are not acidified and sustain bacterial replication [224]. During Y. pestis infection, LC3-I is conjugated with PE to recruit LC3-II, a marker of autophagy progression, to the phagosomal membrane [225]. A similar mechanism is used by Coxiella burnetii , the causative organism of Q fever.…”
Section: Role Of Autophagymentioning
confidence: 99%